Tammam Hasan,s Facilitating Directions in the Light of His Book : The Arabic Language: Meaning and Construction - Hashm Mohammed Mustafa; Shang Mohammed Adeeb M Raouf (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The idea of ​​this research entitled (Tamam Hisan,s Facilitating Directions in the Light of His Book “The Arabic Language: Meaning and Construction”) revolves around the attempts to facilitate and facilitate in Arabic grammar whose motives have emerged in the modern era, and that is an attempt to break free from the constraints of grammatical rules, and the complexity and difficulty that characterized Arabic grammar as a result of that The rules and laws established by the ancient scholars of linguists and grammarians, which made these attempts bold and dangerous because they are attempts to change the dictates of the ancient scholars of laws and grammatical rules in which they spent much effort and took a long time to develop and arrange them. We can say that the most prominent thing that Tamam Hassan dealt with in his book entitled (The Arabic Language Its Meaning and Its Structure) is his call to demolish the theory of the factor in grammar, and to come up with the theory of (the convergence of clues) as an alternative to it. Grammatical.